Reason, religion, and natural law from Plato to Spinoza - Jacobs, Jonathan A. (New York ; Oxford : Oxford University Press, 2013)
This edited volume examines the ways in which theological considerations have figured in natural law theorizing, from Plato to Spinoza. Theological considerations have long had a pronounced role in Catholic natural law theories, but have not been seriously examined from a wider perspective. The contributors to this volume take a more inclusive view of the relation between conceptions of natural law and theistic claims and principles.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Oct. 31, 2012).
Keywords: Natural law -- History; Natural law -- Philosophy